The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/ejcts/ezaa474
|View full text |Cite
|
Sign up to set email alerts
|

Differences in baseline characteristics and outcomes of bicuspid and tricuspid aortic valves in surgical aortic valve replacement

Abstract: OBJECTIVES Patients with bicuspid aortic valve (BAV) comprise a substantial portion of patients undergoing surgical aortic valve replacement (SAVR). Our goal was to quantify the prevalence of BAV in the current SAVR ± coronary artery bypass grafting (CABG) population, assess differences in cardiovascular risk profiles and assess differences in long-term survival in patients with BAV compared to patients with tricuspid aortic valve (TAV). METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Thirty-five studies 7,12,13,[17][18][19][20][21][22][23][24][25][26]28,29,[31][32][33][34]36,39,40,[45][46][47][48][49][50][51]53,[55][56][57][58][59]…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty-five studies 7,12,13,[17][18][19][20][21][22][23][24][25][26]28,29,[31][32][33][34]36,39,40,[45][46][47][48][49][50][51]53,[55][56][57][58][59]…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Nine studies 12 13 17 18 19 20 21 22 23 reported on the prevalence of prior myocardial infarction, which included a total of 6,504 patients. Myocardial infarction was reported in 768 (11.8%) of the total group.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
See 3 more Smart Citations